A Analisis Kebijakan Penanganan Kemacetan Kota Malang Dalam Sudut Pandang Sound Governance - Rafii Assajid, Sulthan; Khoiron; Wulan Sekarsari, Retno (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Congestion is a problem that often occurs in big cities. Malang City, as one of the cities with the second most populous population in East Java, is not free from this traffic jam problem. In dealing with traffic jams, the government has implemented policies such as procuring school buses, traffic engineering, and arranging parking lots. This research focuses on how the Malang city government's policies deal with traffic jams from a Sound Governance perspective by prioritizing five related dimensions, namely process, structure, organization and institutions, policy, and international. This research uses descriptive qualitative methods, so the results found are that the policy for reducing congestion in the city of Malang has not fully prioritized the concept of sound governance. Of the five dimensions, there is an international dimension that has not been fulfilled, so further collaboration is needed from various sectors to get results that meet expectations.